2000
DOI: 10.1103/physrevc.61.064321
|View full text |Cite
|
Sign up to set email alerts
|

Spin-orbit splitting in nonrelativistic and relativistic self-consistent models

Abstract: The splitting of single-particle energies between spin-orbit partners in nuclei is examined in the framework of different self-consistent approaches, nonrelativistic as well as relativistic. Analytical expressions of spinorbit potentials are given for various cases. Proton spin-orbit splittings are calculated along some isotopic chains ͑O, Ca, Sn͒ and they are compared with existing data. It is found that the isotopic dependence of the relativistic mean field predictions is similar to that of some Skyrme force… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
2

Year Published

2001
2001
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 26 publications
1
32
0
2
Order By: Relevance
“…Earlier it was already noted that all standard Skyrme interactions, including the SLy parametrizations that share our fit protocol, have an unresolved trend that overestimates the spin-orbit splittings in heavy nuclei [14,29,98]. Adding the tensor terms, however, further deteriorates the overall description of spin-orbit splittings, instead of improving it.…”
Section: Connection Between Tensor and Spin-orbit Termsmentioning
confidence: 81%
“…Earlier it was already noted that all standard Skyrme interactions, including the SLy parametrizations that share our fit protocol, have an unresolved trend that overestimates the spin-orbit splittings in heavy nuclei [14,29,98]. Adding the tensor terms, however, further deteriorates the overall description of spin-orbit splittings, instead of improving it.…”
Section: Connection Between Tensor and Spin-orbit Termsmentioning
confidence: 81%
“…The neutron and proton spin-orbit splittings E SO = E n,l,j=l−1/2 −E n,l,j=l+1/2 are examined in Fig.5 Various experimental data [23,24] are also shown in Table.1, respectively. The upper and lower triangles are taken from Ref.…”
Section: Finite Nucleimentioning
confidence: 99%
“…It is found that the Fock terms of the σ and ω μ fields strongly contribute to the symmetry energy and increase somewhat the value of K. In contrast, the contribution of pions and, mainly, the contribution of the tensor coupling of the ρ meson produce a major reduction of this magnitude, although, for the coupling constants chosen in [18], K still remains too large (∼460 MeV). Nevertheless, the increase of the KE appears to be quite sensitive to the reduction of K. Further, with the experimental value of the coupling constant f 2 π /4π = 0.08 used, pions produce unrealistic spin-orbit splittings [26] and gaps in the shell model [13,14], which restricts the applicability of the RHFA [18].…”
Section: Results On the Anomalous Ke With Published Relativistic Modelsmentioning
confidence: 95%
“…This can be done, quite simply, in the RHFA [18]. However, if one uses the experimental coupling constant for the Nπ vertex obtained from the NN scattering data (f 2 π /4π ≈ 0.08), the spin-orbit splittings in a family of isotopes seem to exhibit a too strong dependence on A [26]. For example, to fit the experimental results for the splitting of the 1d states of the 48 Ca nucleus, one should reduce the value of f 2 π /4π about 40−60% from its experimental value, i.e., down to f 2 π /4π ≈ 0.05−0.03 (notice that the experimental uncertainty of the spin-orbit splitting for this 1d doublet is not small [26]).…”
Section: Pion Contributionmentioning
confidence: 97%